Pursuing ideological passion in Islamic radical group’s insurgency: a case study of Negara Islam Indonesia - Nur'aini Azizah; Hamdi Muluk; Mirra Noor Milla (Indonesian Journal of Islam and Muslim Societies, 2023)
This study seeks to investigate the ideological passion of those who join a religion-based insurgency group. Religion-based insurgencies continue to exist even after being dispersed, whereas region-based insurgencies typically end after government defeat. Having an ideological hatred for the state’s ideology is the primary motivation for insurgents to fight tenaciously for their movement. This study focuses on the ideological passion formation process in the context of the Indonesian Muslim insurgency known as Negara Islam Indonesia. (NII). NII is a religion-based insurgency in Indonesia that continues to operate clandestinely and is the progenitor of radical movements such as Hizbut Tahrir Indonesia. Using a qualitative approach and a case study procedure, the method was applied. The participants included 21 former NII members. Using thematic analysis, the data was examined. Previous research on religion-based insurgency focused primarily on the role of extremist religious ideology as the movement’s foundation. However, it remains unclear as to how ideology influences the selection of an insurgency strategy and the desire to continue the movement. Formation of ideological passions may cast light on the dynamics of religious insurgency. The findings indicate that the ideological passion of religion-based insurgency is comprised of five primary themes. These five themes are rumination, ideology valuation, movement dedication, social interactions, and ideology internalization. This study highlights the role of ideological passion in the formation of insurgencies. This ideological passion can also play a significant role in the disengagement procedure of insurgents, which includes social interactions and internalization.